Pengaruh Efisiensi Pengelolaan Pembiayaan Pendidikan terhadap Pelaksanaan Program Pendidikan Islam - Achmad Fais Ghozali; Abdullah (Education Reserach Center, 2025)
This study aims to analyze the effect of the efficiency of educational financing management on the implementation of Islamic education programs at Madrasah Diniyah Pondok Pesantren Nurul Jadid. The study employs a quantitative approach, with data collected through questionnaires distributed to 33 respondents who are directly involved in the management and implementation of Islamic education programs, using a saturated sampling (total sampling) technique. The research instrument was developed using a Likert scale and has passed validity and reliability tests. Data analysis was conducted using simple linear regression with the assistance of SPSS software. The results indicate that the efficiency of educational financing management has a positive effect on the implementation of Islamic education programs, with a regression coefficient of 0.380. However, this effect is not statistically significant at the 95 percent confidence level, as indicated by a significance value of 0.083. This suggests that financing management efficiency functions as a supporting factor in the implementation of Islamic education programs, although it is not the primary determining factor. This study emphasizes the importance of a holistic Islamic education management approach by integrating financial management with other managerial factors.